A new species of the antlion genus Euroleon Esben-Petersen from China (Neuroptera: Myrmeleontidae) - Ao, Weiguang; Zhang, Xubo; Ábrahám, Levente; Wang, Xili (Zootaxa, 2009)
According to the Catalog of the World Antlions by Stange (2004), six species of the genus Euroleon Esben-Petersen are reported worldwide, distributed mainly in the Palaearctic Region. Bao and Wang (2006) confirmed that Euroleon coreanus (Okamoto), 1926, Euroleon parvus Hölzel, 1972 and Euroleon polyspilus (Gerstaecker), 1885 occur in China. Euroleon sjostedti Navás, 1928 was discovered in China and denominated by Navás (1928) based on a single male specimen. This species has not again been reported anywhere until now.